Examining E-Payment Adoption Intention Among Indonesian Users: An Extended Technology Acceptance Model Incorporating Risk, Trust, and Religiosity - Siti Nadiatul Istiqomah; Machmudin Eka Prasetya (Journal of Business, Social and Technology, 2026)
Background:  Despite the rapid growth of e-payment transactions in Indonesia, adoption remains uneven due to concerns regarding perceived risk, trust, and religious considerations. Existing Technology Acceptance Model (TAM) studies rarely integrate these socio-cultural factors simultaneously. Objective: The purpose of this study is to examine how users’ intentions to adopt e-payment technology are influenced by perceived usefulness (PU), ease of use (PEOU), risk, trust, and religiosity. Methods: This study employed 193 samples and Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The study’s findings show that users’ intentions to adopt e-payments are significantly influenced by risk, trust, and religiosity factors. On the other hand, users’ intentions do not appear to be significantly impacted by perceived usefulness (PU) or ease of use (PEOU). According to these results, users’ decisions to adopt e-payment technology are dominated by non-technical factors such as perceived risk, degree of system trust, and the influence of religion, even though technical factors such as usefulness and ease of use are generally assumed to influence adoption. Conclusion: The study’s implications highlight the significance of risk management, enhancing confidence in electronic payment systems, and incorporating religious values into the development of marketing strategies. By integrating risk, trust, and religiosity into examining users’ intentions, this study contributes to the development of a modified Technology Acceptance Model. It also helps developers and e-payment service providers better understand the factors affecting users’ adoption of this technology.